Built-in flexibility of taxation and stability when tax liabilities respond with a time lag .2. Reply - Smyth, D.J. (Economic & Social Studies, 1976)
In my earlier paper (Smyth, 1975b) I combined a distributed lag or permanent income consumption function with a lagged tax function. Bradley (1976) disputes my finding that short, two-period, oscillations may result and that consequently the presence of built-in flexibility of taxation may be destabilising rather than stabilising. Bradley reaches his conclusion by limiting consideration to parameter values that he regards as plausible. I shall demonstrate that there is empirical evidence that conflicts with that advanced by Bradley, evidence that gives parameter values consistent with oscillations and destabilisation.
Keywords: Economics; Tax; Ireland